To find the length between the two points \((-2, -1)\) and \((2, 4)\), we can use the distance formula, which is derived from the Pythagorean Theorem. The distance \(d\) between two points \((x_1, y_1)\) and \((x_2, y_2)\) is given by:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Substituting in the points \((-2, -1)\) and \((2, 4)\):
- \(x_1 = -2\)
- \(y_1 = -1\)
- \(x_2 = 2\)
- \(y_2 = 4\)
Now, calculating the differences:
\[ x_2 - x_1 = 2 - (-2) = 2 + 2 = 4 \] \[ y_2 - y_1 = 4 - (-1) = 4 + 1 = 5 \]
Now, substitute these values into the distance formula:
\[ d = \sqrt{(4)^2 + (5)^2} = \sqrt{16 + 25} = \sqrt{41} \]
Calculating \(\sqrt{41}\):
\[ \sqrt{41} \approx 6.403124237 \]
Rounding to the nearest hundredth:
\[ d \approx 6.40 \]
Thus, the length between the two points is approximately 6.40.